Consumer attitudes in the face a lack of CSR in business. The role of age and gender. - Arredondo Trapero, Florina Guadalupe; Tecnológico de Monterrey, México (Pontificia Universidad Javeriana, 2011)
This article analyzes consumer attitudes in the face of lack of corporate social responsibility by gender and age. The theoretical framework established the link between the consumer and corporate social responsibility. In the empirical study, contingency tables are used to test whether the level of demands exerted by consumers is influences by gender and age. Statistical evidence identifies different attitudes in the face of a lack of CSR in companies and the results indicate that the adult woman plays a more decisive part against companies that are not socially responsible.